Screening for occupational exposures and congenital malformations. - Kurppa, Kari; Holmberg, Peter C; Hernberg, Sven; Rantala, K; Riala, Riitta; Nurminen, Tuula (Scandinavian Journal of Work, Environment & Health, 1983)
Since 1976 the Finnish matched-pair Register of Congenital Malformations has been linked to a special project which screens for associations between selected congenital malformations and chemical and physical exposures during early pregnancy. Case mothers and their referents are personally interviewed. Exposure data are quantitated blindly by a team of industrial hygienists and occupational health experts. An analysis of data from 1,047 pairs is now underway. The pairs consist of 289 defects of the central nervous system, 421 orofacial clefts, 200 selected structural malformations of the skeleton, and 137 selected cardiovascular defects. Exposure to organic solvents was associated with defects of the central nervous system in the initial two-year material. However this association was no longer detectable during the following three-year period. More pairs must be gathered before a reasonable judgment regarding the teratogenic potential of solvents becomes possible.